2010
DOI: 10.1371/journal.pone.0008850
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Novel Origin of Replication through Modulating DNA-Protein Interfaces

Abstract: BackgroundWhile the molecular mechanisms of DNA-protein specificity at the origin of replication have been determined in many model organisms, these interactions remain unknown in the majority of higher eukaryotes and numerous vertebrate viruses. Similar to many viral origins of replication, adeno-associated virus (AAV) utilizes a cis-acting origin of replication and a virus specific Replication protein (Rep) to faithfully carry out self-priming replication. The mechanisms of AAV DNA replication are generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…This lack of TRS correlation with RBS is consistent with in vitro experimentation that has found that constraints on this sequence exist but are minimal and difficult to define (22,42,43). Additionally, the spacing between the TRS and RBS as well as secondary structure may contribute to the complexity of determining a TRS influence (19,44). Thus, the presence of a TRS may function in a modest capacity as an independent factor influencing hotspot localization.…”
Section: Hotspots and Rep Binding Sites (Rbs)supporting
confidence: 80%
“…This lack of TRS correlation with RBS is consistent with in vitro experimentation that has found that constraints on this sequence exist but are minimal and difficult to define (22,42,43). Additionally, the spacing between the TRS and RBS as well as secondary structure may contribute to the complexity of determining a TRS influence (19,44). Thus, the presence of a TRS may function in a modest capacity as an independent factor influencing hotspot localization.…”
Section: Hotspots and Rep Binding Sites (Rbs)supporting
confidence: 80%
“…Plasmid pdsEMBL-CMV-E4orf6 (pMH210) was constructed by BamHI excision of the adenovirus E4orf6-coding sequence from pCMVE4orf6 (a kind gift from P. Hearing), treatment with the Klenow fragment to blunt the ends, and ligation into blunt-ended AgeI and NotI sites of pdsEMBLgfp4 (42). Plasmids pDD2-eGFP, pDD5-eGFP, pDD5ϩ2SNS-eGFP, and pDD2ϩ5NS-eGFP have been described previously and consist of a single wild-type or mutant ITR in DD form inserted along with a CMV-eGFP expression cassette into the pUC18 backbone (43,44). Plasmid pTRSn-CMV-eGFP was generated by substitution of a CMV-eGFP expression cassette, flanked by PstI and PciI restriction sites, for the majority of the genome in the snake AAV construct pSAAV (a kind gift from Peter Tijssen) via compatible PstI and NcoI restriction sites (45).…”
Section: Methodsmentioning
confidence: 99%
“…30% of the population is seropositive for AAV-5 specific antibodies (2,5,6). In addition, it is the most divergent AAV yet discovered (4, 7) and, uniquely, does not cross-complement the replication of other serotypes (3,26,27). AAV-2 is known to integrate at a high frequency in the human genome, with preference for a single locus, AAVS1 (15,18,21).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these sequences were separated by an appropriate number of nucleotides and were present in the same orientation as in the AAV-5 ITR. Recent studies have indicated that the AAV-5 ITR spacer and the three-dimensional structure of the terminal resolution site (TRS), where endonuclease cleavage occurs, may be critical to its functionality (27). Therefore, a number of elements critical to AAV-5 ITR function are represented in the newly described consensus integration motif.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation